Phytochemical Studies and Analgesic Activity of Certain Ethno Medicinal Plants of Tripura State, India - CHOUDHURY, RATNA; DATTA CHOUDHURY, MANABENDRA; DE, BIPLAB; BHUSAN PAUL, SATYA (Asian Journal of Chemistry, 2010)
Methanolic extract of edible parts of certain plants (10 Nos.), growing in Tripura state, India, which are used by tribal people of Tripura, were able to exhibit analgesic activity in mice. Among them S. torvum showed comparable activity to the standard drug aspirin. Extracts were containing alkaloids and some other chemical constituents.